BOARD INDEPENDENCE, KINERJA SUPPLY CHAIN DAN KINERJA PERUSAHAAN - Sutrisno, St (Paradigma, 2015)
The aim of this study is to get a better understanding on the relationship between board independence and firm performance by considering supply chain performance as the contextual factor. Supply chain and firm performance variables in this study are taken from financial reports of manufacture based company listed in The Indonesia Stock Exchange.Using moderated regression analysis, the result supports the hyphotesis that supply chain performance moderates the relationship between board independence and firm performance. Result of this study shows that, in this globalization era, board independence can only be increasing firm performance when company effectively applying competitive strategy of differentiation by which it is manifested in its supply chain performance.Â Keywords: board independence, supply chain performance, firm performance, independent directors, outside directors, good corporate governance, competitive strategy.Â